Riješite (x + 1) (x + 3) (x + 4) (x + 6) = 112?

Riješite (x + 1) (x + 3) (x + 4) (x + 6) = 112?
Anonim

Odgovor:

# X = -7/2 + -isqrt31 / 2 # ili # X = -7/2 + -sqrt57 / 2 #

Obrazloženje:

Dozvolite grupi LHS as

# (X + 1) (x + 6) (X + 3) (x + 4) = 112 #

# => (X ^ 2 + 7x + 6) (x ^ 2 + 7x + 12) = 112 #

Sada pusti # U = x ^ 2 + 7x # i tada iznad postaje jednadžba

# (Z + 6) (u 12 +) = 112 #

ili # U ^ 2 + 72 + 18u = 112 #

ili # U ^ 2 + 18u 40 = 0 #

ili # (Z + 20) (u-2) = 0 # tj # U = 2 # ili #-20#

Kao takva # 2 x ^ + 7x + 20 = 0 # tj #x = (- 7 + -sqrt (7 ^ 2-80)) / 2 # tj # X = -7/2 + -isqrt31 / 2 #

ili # 2 x ^ + 7x-2-0 # tj #x = (- 7 + -sqrt (7 ^ 2 + 8)) / 2 # tj # X = -7/2 + -sqrt57 / 2 #